Liver fibrosis and fatty liver as independent risk factors for cardiovascular disease. Issue 10 (8th July 2021) - Tamaki, Nobuharu; Kurosaki, Masayuki; Takahashi, Yuka; Itakura, Yoshie; Inada, Kento; Kirino, Sakura; Yamashita, Koji; Sekiguchi, Shuhei; Hayakawa, Yuka; Osawa, Leona; Higuchi, Mayu; Takaura, Kenta; et al.
Abstract: Background and Aim: The association between liver fibrosis, fatty liver, and cardiovascular disease (CVD) risk is unknown. Hence, this study aimed to investigate the association of liver fibrosis and fatty liver with CVD risk independent of already known CVD risk comorbidities. Methods: This is a prospective study registered with the University Hospital Medical Information Network clinical trial registry (UMIN000036175). Liver fibrosis was assessed by serum fibrosis markers including FIB‐4, nonalcoholic fatty liver disease fibrosis score (NFS), and Wisteria floribunda agglutinin‐positive Mac‐2 binding protein (WFA + ‐M2BP), whereas fatty liver was diagnosed by ultrasonography. CVD risk was evaluated using the Framingham risk score (FRS), and a high CVD risk was defined as an FRS ≥ 20%. Results: A total of 3512 subjects were enrolled, and high CVD risk (FRS ≥ 20%) was observed in 17.5%. Advanced fibrosis (FIB‐4 ≥ 2.67, NFS ≥ 0.675, and WFA + ‐M2BP ≥ 1.0) and the presence of fatty liver were significantly associated with high CVD risk independent of diabetes mellitus, dyslipidemia, and hypertension. When subjects were stratified by liver fibrosis and fatty liver, subjects with advanced fibrosis and fatty liver have the highest odds for high CVD risk (odds ratio [OR]: 5.90–35.6), followed by subjects with advanced fibrosis and without fatty liver (OR: 2.53–9.62) using subjects without advanced fibrosis and fatty liver as a reference. Conclusions: Liver fibrosis and fatty liver were associated with CVD risk independent of already known CVD risk comorbidities. The assessment of liver fibrosis and fatty liver may be useful to identify high CVD risk subjects.